REPROGRAMMING CELL DEATH PATHWAYS FOR THERAPEUTIC GAIN (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Failure of conventional therapies in cancer inflammatory and degenerative diseases is frequently driven by resistance to cell death rather than lack of target engagement. Regulated cell death pathways beyond apoptosis have therefore gained increasing clinical relevance as therapeutic targets capable of overcoming treatment resistance or limiting tissue injury. Methods: Open access PubMed indexed studies evaluating pharmacological or molecular modulation of regulated cell death pathways were systematically reviewed. Thirteen experimental studies with therapeutic intent and mechanistic validation were included and synthesized to assess clinical relevance and translational potential. Results: Apoptosis directed therapies achieved tumor regression but were commonly undermined by resistance mechanisms. Targeting necroptosis and pyroptosis reduced inflammatory tissue damage in ischemic and immune mediated conditions while promoting immunogenic tumor cell death in apoptosis resistant cancers. Ferroptosis targeting demonstrated marked efficacy in therapy refractory malignancies and protective effects in neurodegenerative models. Combination and network level targeting strategies consistently outperformed single pathway interventions. Conclusions: Therapeutic modulation of regulated cell death pathways offers clinically actionable opportunities to overcome resistance and tailor disease specific interventions. Translation into patient benefit will depend on biomarker guided pathway selection and rational combination strategies.